Contesting Misogyny in Canonical Hadith: A Comparative Analysis of the Commentaries of Ibn Ḥajar al-‘Asqalānī and Badr al-Dīn al-‘Aynī on Ṣaḥīḥ al-Bukhārī - Samanarnik, Samanarnik; Muhammad Saifullah; Muhammad Amiruddin (Journal of Ushuluddin and Islamic Thought, 2024)
This study examines the controversy surrounding authentic hadiths that reflect gender bias, misogyny, and anti-female sentiment, with a particular focus on Ṣaḥīḥ al-Bukhārī, one of the most authoritative sources of Islamic law. Specifically, this study highlights how two major commentators on Ṣaḥīḥ al-Bukhārī, Ibn Ḥajar al-‘Asqalānī and Badr al-Dīn al-‘Aynī, interpret hadiths that depict women as the majority of hell’s inhabitants and their understanding of the term kufr in that context, as explained in their major works, Fatḥ al-Bārī and ‘Umdat al-Qārī. This study also investigates the historical context of the two scholars, paying attention to their differing views and personal conflicts, as well as the impact of these on their interpretation of the hadith. Through a qualitative literature review approach, this study seeks to provide a deeper understanding of their methods of interpretation and highlights the presence of personal conflict as a factor shaping interpretive differences. This study argues that the competitive dynamics between Ibn Ḥajar al-‘Asqalānī and Badr al-Dīn al-‘Aynī significantly influenced how each scholar understood this controversial narration, resulting in different readings of the hadith narrative that is often considered misogynistic.